Comparison of friction coefficient of static and sliding determination methods: conventional, video tracking and IoT-based - Gideon, Samuel; Sumarti, Heni (Universitas Sultan Ageng Tirtayasa, 2024)
The prevalent physics parameter in the concepts of friction are the friction coefficient of static and sliding. The objective of this research is to determine the friction coefficient of static and sliding by means of conventional measurement, video-tracking as well as proposed IoT-based measurement likewise to compare the results of each methods correspondingly theoretical references. Two universal systems in determining friction coefficient of static and sliding are reproduced, involves both conventional and IoT-based measuring instruments: flat block against flat runway and flat block against inclined runway. Video-tracking is the most precise between conventional and IoT-based method as its %RSD mean value of interval reading and angle of inclination respectively 6.22% and 0.88%. In case determination of friction coefficient of static three methods have equal %TE mean value of 22.85% for oak-based block on cast iron plank excluded slightly 0.49% of differences than assumed %TE value of video-tracking. Each methods are considerably accurate since each friction coefficient of sliding are theoretical values required range of 0.300 – 0.500. for oak-based block on cast iron plank IoT-based measurement has the smallest mean value of %TE indicating most accurate between two other methods.